Drivers of Seasonal Variability in Marine Boundary Layer Aerosol Number Concentration Investigated Using a Steady State Approach. Issue 2 (21st January 2018) - Mohrmann, Johannes; Wood, Robert; McGibbon, Jeremy; Eastman, Ryan; Luke, Edward
Abstract: Marine boundary layer (MBL) aerosol particles affect the climate through their interaction with MBL clouds. Although both MBL clouds and aerosol particles have pronounced seasonal cycles, the factors controlling seasonal variability of MBL aerosol particle concentration are not well constrained. In this paper an aerosol budget is constructed representing the effects of wet deposition, free‐tropospheric entrainment, primary surface sources, and advection on the MBL accumulation mode aerosol number concentration ( N a ). These terms are then parameterized, and by assuming that on seasonal time scales N a is in steady state, the budget equation is rearranged to form a diagnostic equation for N a based on observable variables. Using data primarily collected in the subtropical northeast Pacific during the MAGIC campaign (Marine ARM (Atmospheric Radiation Measurement) GPCI (GCSS Pacific Cross‐Section Intercomparison) Investigation of Clouds), estimates of both mean summer and winter N a concentrations are made using the simplified steady state model and seasonal mean observed variables. These are found to match well with the observed N a . To attribute the modeled difference between summer and winter aerosol concentrations to individual observed variables (e.g., precipitation rate and free‐tropospheric aerosol number concentration), a local sensitivity analysis is combined with the seasonal difference in observed variables. This analysis shows that despite wintertime precipitation frequency being lower than summer, the higher winter precipitation rate accounted for approximately 60% of the modeled seasonal difference in N a, which emphasizes the importance of marine stratocumulus precipitation in determining MBL aerosol concentrations on longer time scales. Key Points: Subtropical NE Pacific marine aerosol number concentration shows strong seasonality, as do many of the drivers of aerosol variability A steady state model of MBL aerosol number concentration reproduces most of the observed seasonal difference (summer versus winter) The model is used to show that higher winter mean precipitation rate is the most important factor in determining the seasonal difference